Bacteria‐sediment associations in an alpine, freshwater environment and their effects on particle size, density and settling velocity. Issue 10 (9th May 2018) - Barrett, David C.; Hodder, Kyle R.
Abstract: This study measures the presence of bacteria‐sediment associations (BSAs) in an alpine, glacier‐fed watershed in the Southern Coast Mountains of British Columbia, Canada. The impact of BSAs on the creation of flocculated particles and their settling velocity are quantified using a laser transmissometer. Results from the study indicate that BSAs are present in the watershed and vary over both space and time. The percentage of bacteria associated with sediment particles was found to range from < 1% to 40%. Major sources of planktonic bacteria such as agricultural land and wastewater treatment outflow co‐occur with large decreases in the BSA ratio. Laboratory analysis demonstrates that an increase in the concentration of bacteria was associated with a decrease in the volume concentration of small particles, and a decrease in both estimated density and measured settling velocity for particles in larger size classes; consistent with flocculated particles of increasing complexity arising from combinations of primary particles and/or BSAs. Paleoenvironmental reconstructions using laminated lake sediments in alpine, glacier‐fed systems benefit from a fuller understanding of the geomorphologic processes by which they formed. While bacteria are noted to enhance formation of flocculated particles in laboratory systems, their impact upon geomorphic processes in natural systems have yet to be fully explored. © 2018 The Authors. Earth Surface Processes and Landforms published by John Wiley & Sons Ltd. Abstract : Through a suite of in situ and experimental methods, it is found that bacteria–sediment associations are both common in an alpine freshwater environment and that they affect the settling velocity of sediment through the creation of composite particles (flocculation).